2005
DOI: 10.1063/1.1926285
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of valence orbitals of propene by electron momentum spectroscopy

Abstract: The binding energy spectra and momentum distributions of all valence orbitals of propene were studied by electron momentum spectroscopy (EMS) as well as Hartree-Fock and density functional theoretical calculations. The experiment was carried out at impact energies of 1200 eV and 600 eV on the state-of-the-art EMS spectrometer developed at Tsinghua University recently. The experimental momentum profiles of the valence orbitals were obtained and compared with the various theoretical calculations. Moreover, the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…The EMS binding energy spectra from the measurement were deconvoluted using a least-squares fit according to Bevington and Robinson 25 into Gaussians with fixed peak widths and positions but variable Gaussian heights (relative cross-sections). The procedure of extracting experimental MDs from those angular resolved energy spectra can be found in our previous work . In addition, the normalization of the measured orbital momentum distributions to the simulated in the theory is one of the general normalization methods used in the EMS field, employed by the Brion group at the University of British Columbia. , The procedure is to compare the experimental MDs with theoretical ones; the observed MDs were divided by a normalized constant to give a best fit.…”
Section: Methodsmentioning
confidence: 99%
“…The EMS binding energy spectra from the measurement were deconvoluted using a least-squares fit according to Bevington and Robinson 25 into Gaussians with fixed peak widths and positions but variable Gaussian heights (relative cross-sections). The procedure of extracting experimental MDs from those angular resolved energy spectra can be found in our previous work . In addition, the normalization of the measured orbital momentum distributions to the simulated in the theory is one of the general normalization methods used in the EMS field, employed by the Brion group at the University of British Columbia. , The procedure is to compare the experimental MDs with theoretical ones; the observed MDs were divided by a normalized constant to give a best fit.…”
Section: Methodsmentioning
confidence: 99%
“…Electron momentum spectroscopy is known to be a powerful method for experimentally reconstructing valence orbital densities [16,17,[20][21][22][23][24][25]. Previous studies combining EMS experiments with theoretical modelling have shown that with this powerful spectroscopic technique, it is also possible to experimentally study the influence of the molecular conformation onto the spread, shape and topology of molecular orbitals [26][27][28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%